РОЛЬ МАРКЕРА КОСТНОГО РЕМОДЕЛИРОВАНИЯ ОСТЕОКАЛЬЦИНА В РЕГУЛЯЦИИ ЭНЕРГЕТИЧЕСКОГО ГОМЕОСТАЗА ПРИ САХАРНОМ ДИАБЕТЕ 2 ТИПА - Ковальчук А. В.; Зиныч О. В.; Корпачев В. В.; Кушнарева Н. Н.; Прибила О. В. (World Science, 2020)
Osteocalcin (OK) is actively involved in the humoral regulation of energy homeostasis. However, the relationship between the level of OK as a modulator of metabolic processes and constitutional and metabolic features in patients with type 2 diabetes mellitus (DM) of a different gender remains not thoroughly studied. The study included 127 patients with type 2 diabetes ≥ 50 years of age. Of these, 70 were postmenopausal women and 57 men. It was found that in the general group of women, the concentration of OK in the blood serum was significantly higher than in men. The observed difference is due to significantly higher levels of OK in women of the older age group (≥ 60 years) in comparison with men. At the same time, a decrease in bone mineral density (BMD) in the femoral neck was observed in subgroups of men and women aged ≥ 60 years and older, while in the younger subgroups of patients, the BMD of lumbar and femoral zones were close to each other. The relationships between OK levels and adipose tissue parameters, evaluated by calculating the morphological and functional index of visceral obesity (IVO), were investigated. An increase in the OK level in the groups of men and women was accompanied by a decrease in the IVO values. The highest degree of insulin resistance was determined in groups of patients with minimal levels of OK and high IVO, and the lowest values were recorded in patients with high levels of OK and low IVO. The decrease of the blood OK level in patients with type 2 diabetes occurs in parallel with an increase in the degree of insulin resistance and dysfunction of visceral adipose tissue. In this case, IVO is a more accurate parameter reflecting the constitutional and metabolic phenotypic changes, compared with the index of the waist circumference. The decrease in BMD in patients with type 2 diabetes is the result of predominantly involutive processes that are noticeable at the age of ≥ 60 years and occur against the background of a decrease in the content of OK with age.